The current state of the shelter belts of the Kherson region (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The article analyzes the complex factors that affect the current state of shelterbelts in the Kherson region. In recent decades because of conflicts of interests of forestry and farmers forest belts don’t have clearly defined users. Because of this fundamental research of the current state and functional compliance of shelterbelts is not being performed now. As a result of our research we have identified dependence of the quality of the current state of shelterbelts on their species composition, type of construction, the underlying surface and intensity of farming on nearby farmland. When laying sample plots it was covered all types of shelterbelts of the Kherson region, based on their species composition and the soil type. Separately, our research has shown that the surface layers – herbaceous and moss-lichen – play a significant positive role in the "independent" existence of shelterbelts. It lies in the fact that the larger the area of projective cover and therefore powerful litter – the better the moisture content of soil is. This, in turn, has its positive impact on moisture content of phanerophytes, and the possibility of a self-renovation by generative and vegetative means. It was identified that the reduction of anthropogenic impact on the adjacent fields there is a tendency to almost complete replacement of grassy tiers and soil conditions of the forest belt ecosystem. It was indicated that shelterbelts in the South of Ukraine plays a crucial role in the structure of ecological network of Ukraine, where they are the only environmental migration corridors and gene pool exchange of native plant and animal species on upland areas.
Keywords: shelter belts, species composition, tier, current state, Kherson region.